Chlorophyll Fluorescence Spectra as an Indicator of X-Ray + EMS-Induced Phytotoxicity in Safflower. Issue 4 (13th June 2012) - Pandey Pandey, Jitendra Kumar Jitendra Kumar; Srivastava Srivastava, Preeti Preeti; Yadav Yadav, Ram Singh Ram Singh; Gopal Gopal, Ram Ram
Abstract : The present investigation deals with the study of in vivo laser-induced chlorophyll florescence spectra (LICF) of safflower leaves ( Carthamus tinctorius L.) for X-rays+ EMS-treated plants. Seeds were treated with different doses of X-ray+ EMS (5, 8, 12, 25, and 30 Kr+ 0.5% EMS) and were grown in the green house. The effects of the concerned treatment on chlorophyll (Chl) contents and Chl fluorescence were investigated after 7 days of germination. Results obtained revealed that the values of Chl contents, intensity of Chl fluorescence spectra, and fluorescence intensity ratio (FIR) F685/F730 are directly correlated with the treatment doses monitored. The treatment sets of 8, 12, and 25 Kr + 0.5% EMS doses showed an increase in FIR and thereby a decrease in the Chl contents. However, the lowest treatment dose of 5 Kr + 0.5% showed a decrease in FIR and thereby an increase in chlorophyll contents. Safflower seeds treated with 30 Kr + 0.5% EMS were proved to be lethal as they showed no germination. Thus, our study demonstrates early detection of chlorophyll damage caused by various physical and chemical mutagens through the application of LICF spectra.